Heptamethoxyflavone, a citrus flavonoid, suppresses inflammatory osteoclastogenesis and alveolar bone resorption. Issue 1 (2nd January 2015) - Matsumoto, Chiho; Inoue, Hiroki; Tominari, Tsukasa; Watanabe, Kenta; Hirata, Michiko; Miyaura, Chisato; Inada, Masaki
Abstract: We examined the effects of heptamethoxyflavone (HMF), a citrus flavonoid on inflammatory bone resorption. HMF suppressed the osteoclast formation and PGE2 production induced by IL-1. In mouse calvarial organ cultures, HMF attenuated the bone resorption elicited by LPS. HMF suppressed bone resorption in the mandibular alveolar bone. HMF may protect against inflammatory bone loss such as periodontal disease.